2011
DOI: 10.1016/j.antiviral.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpes activity of glucoevatromonoside, a cardenolide isolated from a Brazilian cultivar of Digitalis lanata

Abstract: Cardiac glycosides, known ligands of the sodium pump, are widely used in the treatment of heart failure, such as digoxin and digitoxin. Besides this important activity, other biological activities, such as the antiviral activity, have been described for this group. HSV are responsible for many infections of oral, ocular and genital regions. Treatment with nucleoside analogs such as acyclovir is effective in most cases; however drug-resistance may arise due to prolonged treatment mainly in immunocompromised ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 32 publications
7
59
0
1
Order By: Relevance
“…A time-of-addition study was performed using a virus yield reduction assay as reported by Silva et al with minor modifications [27]. Briefly, confluent Vero or GMK AH1 cell monolayers were inoculated with 100 PFU of HSV-1 (KOS strain) per well and incubated at 37°C for 1 h. After removing viruses, cells were maintained at 37°C and treated with genistein (40 lM), coumestrol (40 lM) or ACV (20 lM) at 1, 2, 3, 4, 6, 8, 10, 12, 16, 18 and 24 h postinfection (p.i.).…”
Section: Time-of-addition Assaymentioning
confidence: 99%
See 4 more Smart Citations
“…A time-of-addition study was performed using a virus yield reduction assay as reported by Silva et al with minor modifications [27]. Briefly, confluent Vero or GMK AH1 cell monolayers were inoculated with 100 PFU of HSV-1 (KOS strain) per well and incubated at 37°C for 1 h. After removing viruses, cells were maintained at 37°C and treated with genistein (40 lM), coumestrol (40 lM) or ACV (20 lM) at 1, 2, 3, 4, 6, 8, 10, 12, 16, 18 and 24 h postinfection (p.i.).…”
Section: Time-of-addition Assaymentioning
confidence: 99%
“…Subsequently, the potential antiherpes activity was evaluated using a plaque number reduction assay as described previously by Silva et al [27]. Confluent monolayers of Vero or GMK AH1 cells were infected with 100 PFU per well of HSV-1 (KOS and 29R strains) or HSV-2 (strain 333), respectively, for 1 h at 37°C.…”
Section: Antiherpes Evaluationmentioning
confidence: 99%
See 3 more Smart Citations